2021
DOI: 10.1108/ijph-09-2020-0065
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the views of people in custody about the management of the COVID-19 pandemic in the Scottish Prison Estate

Abstract: Purpose The purpose of this paper is to foreground and analyse the views of people in custody about the management of the COVID-19 pandemic within the Scottish Prison Estate. The project is unique in using a correspondence participatory action methodology to engage with a group of people in custody at one Scottish prison. Design/methodology/approach At the time of ethical approval (early April 2020), all face-to-face research projects facilitated by the Scottish Prison Service were paused. In response to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 60 publications
0
44
0
2
Order By: Relevance
“…The majority of papers were opinion pieces, with the exception of 10 case studies, [30][31][32][33][34][35][36][37][38][39] seven guidelines, 13-16 40-42 six literature reviews, [43][44][45][46][47][48] five qualitative studies, [49][50][51][52][53] three cross-sectional studies, [54][55][56] three briefings, [57][58][59] three case studies 37 39 60 and one study protocol. 61 All assessed studies were found to be of poor quality (see online supplemental appendix 3).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of papers were opinion pieces, with the exception of 10 case studies, [30][31][32][33][34][35][36][37][38][39] seven guidelines, 13-16 40-42 six literature reviews, [43][44][45][46][47][48] five qualitative studies, [49][50][51][52][53] three cross-sectional studies, [54][55][56] three briefings, [57][58][59] three case studies 37 39 60 and one study protocol. 61 All assessed studies were found to be of poor quality (see online supplemental appendix 3).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of qualitative research on Covid-19 more widely, the responses to letter two shaped later correspondence between the PI and participants, reported elsewhere (Maycock, 2021;Maycock & Dickson, 2021), and it is hoped that the letters that came after letter two were ones that resonated with areas that the participants felt were important. In this sense, we can clearly see the impacts of the participants responses analysed in this paper in relation to the direction of the research project from letter two onwards.…”
Section: Conclusion -To What Extent Can Qualitative Correspondence Me...mentioning
confidence: 92%
“…The findings of this study have been published elsewhere (Maycock, 2021; Maycock & Dickson, 2021), these focus on the reflections of people in custody about the ways in which the Covid-19 pandemic and lockdown have been managed within a Scottish prison. Additionally, a more theoretical paper analyses the ways in which the Covid-19 lockdown increased feelings of isolation and the ‘depth’ of prison sentences for the participants in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Like many other total institutional settings, prisons have remained key hotspots for the spread of the novel coronavirus disease (COVID-19) since its declaration as a Public Health Emergency of International Concern (WHO, 2020 ; Cingolani et al, 2020 ; Pettus-Davis et al, 2021 ). Prisoners have been recognized as more susceptible to the virus compared to the general population (Maycock & Dickson, 2021 ; Mhlanda-Gunda et al 2022 ). Similarly, Braithwaite et al ( 2021 ) explain that overcrowding in prisons coupled with the convoluted human communication patterns in prison facilities have accounted for the spike in the prevalence of COVID-19 in such settings globally.…”
mentioning
confidence: 99%
“…The United Nations Office on Drugs and Crime (UNODC) has, therefore, been very categorical on the need for all UN member countries to incorporate prisons, prisoners, and prison workers into COVID-19 public health responses (Reuters, 2021 ). However, lack of compliance and privation of thorough preparedness on the path of most countries, have resulted in unprecedented death cases in prisons across the globe (Franco-paredes et al, 2020 ; Maycock & Dickson, 2021 ). For instance, according to The Marshall Project ( 2021 ), about 275,000 prisoners have contracted the virus in the United States, with over 1700 of them losing their lives.…”
mentioning
confidence: 99%